Balancing exploration and exploitation of IT resources: the influence of Digital Business Intensity on perceived organizational performance. Issue 5 (1st September 2017) - Nwankpa, Joseph K.; Datta, Pratim
Abstract: Facing a barrage of novel information technology (IT), organizations must invest on the basis of the impact of IT capabilities on the organization's performance. This research extends Bharadwaj's ( MIS Quarterly 169–196, 2000 ) resource-based view of the relationship between IT capability and performance by introducing both the mediating and moderating effects of Digital Business Intensity (DBI). Empirical data collected from CIO's from US firms reveal that although IT capability positively influences organizational performance, this relationship may differ in strength at different levels of DBI. Our study also finds that IT capability is important in determining DBI, which in turn influences organizational performance. Findings highlight tensions between DBI exploration and IT capabilities exploitation. Results also suggest that companies that leverage their existing IT capabilities to drive DBI are more adept at securing performance returns. However, when DBI investments do not complement existing IT capabilities, DBI appears to dampen performance, further accentuated for high-DBI firms.